Appendix 5.13: Executive Order 879, Directing the Propagation of the Filipino Ideology and Creating a Committee to Evolve, Supervise and Monitor the Implementation of the Program for Its Dissemination - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
As early as 1972, President Marcos talked about formulating a Filipino Ideology in his diaries. Then in 1979, a book was released under his name (but also “ghosted”; see Teodoro 2008) entitled Towards a Filipino Ideology . This was followed by An Ideology for Filipinos (1980). Why Marcos waited until March 1983 to require instruction on the Filipino Ideology “among [government] personnel and the general public they serve”; to mandate prospective civil servants to have “basic knowledge on the Filipino Ideology”; and to order the Ministry of Education, Culture, and Sports to look into how to integrate the Filipino Ideology into all school curricula remains to be surfaced. Marcos clearly aimed to form a bureacracy with a uniform “ideological” orientation, as well as to indoctrinate students in “all levels of education and training and all schools in the country” in “Marcosian” thought. It would be interesting to discover how many of today’s Marcos loyalists recall undergoing seminars on the Filipino Ideology or learning about it from their teachers or instructors in the 1980s.